AN ACCOUNT ON THE CECROPIA SPECIES (CECROPIACEAE) OF PERU - BERG CORNELIS C. (Caldasia)
A survey and a key to the Cecropia species of Peru are presented with notes on distribution, ecology, and myrmecophily. A new Peruvian species is described: C. chlorostachya.